Pengaruh Persepsi Keadilan Distributif pada Penilaian Kinerja Terhadap Kinerja Karyawan yang Dimediasi oleh Kepuasan Penilaian Kinerja di PT. Dok dan Perkapalan Surabaya - Anang Kistyanto, Fajru Achmi Fauziah (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2016)
The purpose of this research is to examine and analyze the effect of distributive justice onperformance appraisal to work performance through performance appraisal satisfaction (study onPT. Dok dan Perkapalan Surabaya). This type of research is a causality research studies, with thequantitative approach. This research was using simple random sampling. This research used asample of 137 respondents was drawn from employees of PT. Dok dan Perkapalan Surabaya inProduction Department. The result was based on path analysis method showed that there was asignificant direct effect distributive justice on performance appraisal to performance appraisalsatisfaction and performance appraisal satisfaction to work performance. But there was notsignificant direct effect distributive justice of performance appraisal on work performance.